A revision of the genus Stictobura Crotch and description of a new species of Sticholotis Crotch (Coleoptera: Coccinellidae: Sticholotidinae) - Poorani, J.; Vandenberg, Natalia J.; Booth, R. G. (Zootaxa, 2011)
The species of Stictobura Crotch (1874) (Coccinellidae: Sticholotidinae) are revised. Stictobura gibbula (Weise, 1908) indeed belongs to Sticholotis Crotch (1874) under which it was originally described (stat. rev.) and is removed from Stictobura. Stictobura buruensis Korschefsky (1944) is transferred to Sticholotis (new combination). Lectotypes are designated for Sticholotis (Apterolotis) andrewesi Weise (1908), Sticholotis (Apterolotis) gibbula Weise (1908), Stictobura semipolita Sicard (1911), and Stictobura rubroguttata Sicard (1925). The species of Stictobura are keyed and notes on biology are provided wherever available. Sticholotis magnostriata sp. n., which is externally similar to the species of Stictobura, is described from India (Assam).